2015
DOI: 10.3844/ajavsp.2015.212.216
|View full text |Cite
|
Sign up to set email alerts
|

Leukemia Inhibitory Factor (<i>LIF</i>) Gene Polymorphism and its Impact on Reproductive Traits of Pigs

Abstract: The purpose of this study was to determine the frequencies of alleles and genotypes of the Leukemia Inhibitory Factor (LIF) gene (ID: 399503) in Landrace, Large White and Duroc pigs in Russia and to evaluate the impact on productive traits of pigs. Polymorphism was genotyped using PCR-RFLP method. In the course of studies we observed a different distribution of allele and genotype frequencies of different breeds. In all breeds under study all three genotypes AA, AB, BB were determined. The results of this stud… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
4
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(8 citation statements)
references
References 14 publications
3
4
0
Order By: Relevance
“…The porcine LIF c.*24C was the major allele in these pig populations. These results are agreed with previous studies, which showed that the porcine LIF c.*24C was a major allele in several pig breeds such as German Landrace (Spötter et al, 2009), Large White (Leonova et al, 2015), and four Chinese pig breeds (Ding et al, 2020). However, the porcine LIF c.*24T was the major allele in German synthetic line (Spötter et al, 2005), German Large White (Spötter et al, 2009), Polish Large White and Polish Landrace (Mucha et al, 2013), and Landrace and Duroc (Leonova et al, 2015).…”
Section: Discussionsupporting
confidence: 92%
See 1 more Smart Citation
“…The porcine LIF c.*24C was the major allele in these pig populations. These results are agreed with previous studies, which showed that the porcine LIF c.*24C was a major allele in several pig breeds such as German Landrace (Spötter et al, 2009), Large White (Leonova et al, 2015), and four Chinese pig breeds (Ding et al, 2020). However, the porcine LIF c.*24T was the major allele in German synthetic line (Spötter et al, 2005), German Large White (Spötter et al, 2009), Polish Large White and Polish Landrace (Mucha et al, 2013), and Landrace and Duroc (Leonova et al, 2015).…”
Section: Discussionsupporting
confidence: 92%
“…Moreover, the porcine LIF gene is located closely with the QTL regions for total number born alive (37.5-38.5 Mb), total number born (41.8-42.0 Mb), and total litter weight (56.4-56.6 Mb) (Onteru et al, 2012;Schneider et al, 2012). Additionally, significant associations of the porcine LIF polymorphism with litter traits have been reported in several pig breeds (Spötter et al, 2005;Lin et al, 2009;Spötter et al, 2009;Mucha et al, 2013;Leonova et al, 2015;Ding et al, 2020). All these shreds of evidence indicated that the LIF function was critical for embryonic implantation and embryonic survival.…”
Section: Introductionmentioning
confidence: 96%
“…Reproductive traits have been strongly selected in the last years to increase the production, especially in maternal lines, where the fertility and morphology of the sows are fundamental for a large litter size. Important genes were identified involving reproductive traits such as LIF , which plays a role on total number of piglets born in Landrace, Large White and Duroc breeds [27], and the genes ZNRF3 and KREMEN1 , which have been associated with waist-hip ratio and sexual dimorphism in the genetic basis of fat distribution [28]. Studies with pigs using other methodologies, have also identified significant portions of selection signatures that coincide with loci that control biological processes related to behavioral and reproductive traits, which may have been favored by the selection process [2930].…”
Section: Discussionmentioning
confidence: 99%
“…The farm specializes in breeding purebred pigs Landrace, Large White and Duroc. The Landrace and Large White breeding are aimed at improving the reproductive traits and Duroc is on growth and meat (Leonova et al, 2015). All pigs were kept under identical and standard conditions.…”
Section: Animalsmentioning
confidence: 99%